Self-Regulated Learning Skill Levels Among 12th Grade (General Diploma) Students in the Sultanate of Oman - Al-Siyabi, Salama Saif Hamed (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to know the levels of self-regulated learning skills (SRL) among twelfth grade students in the Sultanate of Oman. It also sought to reveal the existence of differences between students in these skills due to the gender and the academic stream. The study sample consisted of (190) twelfth grade students from two schools in the Wilayyat of Bidbid in Al Dakhiliyah Governorate in the Sultanate of Oman. The researcher used the Purdie scale; it included four dimensions. The findings of the study resulted in students possessing moderate to high levels of SRLS. The study also found that the highest level of SRLS was in the recitation and memorization dimension. It was also found that students possessing an average level of SRLS based on record keeping. It was striking that there were no significant differences due to study variables gender and academic stream.